2019
DOI: 10.3390/molecules24091775
|View full text |Cite
|
Sign up to set email alerts
|

How Melittin Inserts into Cell Membrane: Conformational Changes, Inter-Peptide Cooperation, and Disturbance on the Membrane

Abstract: Antimicrobial peptides (AMPs), as a key component of the immune defense systems of organisms, are a promising solution to the serious threat of drug-resistant bacteria to public health. As one of the most representative and extensively studied AMPs, melittin has exceptional broad-spectrum activities against microorganisms, including both Gram-positive and Gram-negative bacteria. Unfortunately, the action mechanism of melittin with bacterial membranes, especially the underlying physics of peptide-induced membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 117 publications
(196 reference statements)
1
68
0
Order By: Relevance
“…The use of apitoxin, especially its main compound melittin, as a novel cancer-treatment strategy has gained wide importance recently [70,71]. In fact, melittin is known to be a nonspecific cytolytic peptide that can attack the lipid bilayer, thus leading to a significant toxicity when injected intravenously [72]. Nevertheless, many optimization approaches, including the use of nanoparticle-based delivery of melittin, have been exploited.…”
Section: Bioactivities and Therapeutic Applications Of Bee Venom Amentioning
confidence: 99%
See 1 more Smart Citation
“…The use of apitoxin, especially its main compound melittin, as a novel cancer-treatment strategy has gained wide importance recently [70,71]. In fact, melittin is known to be a nonspecific cytolytic peptide that can attack the lipid bilayer, thus leading to a significant toxicity when injected intravenously [72]. Nevertheless, many optimization approaches, including the use of nanoparticle-based delivery of melittin, have been exploited.…”
Section: Bioactivities and Therapeutic Applications Of Bee Venom Amentioning
confidence: 99%
“…Nevertheless, many optimization approaches, including the use of nanoparticle-based delivery of melittin, have been exploited. Remarkably, the crude BV as well as melittin have shown antitumor activities against different cancer cell types including breast, liver, leukemia, lung, melanoma, and prostate cancer cells [70,72,73,74,75]. Wang et al [76] investigated the mechanism behind melittin antitumor activity and showed that melittin can induce apoptosis of hepatocellular carcinoma cells (HCC) through the activation of the CAMKII-TAK1-JNK/p38 signaling pathway (CAMKII: Ca 2+ /calmodulin-dependent protein kinase; TAK1: Transforming growth factor-beta-activated kinase 1; JNK/p38: Mitogen-activated protein kinases).…”
Section: Bioactivities and Therapeutic Applications Of Bee Venom Amentioning
confidence: 99%
“…Recent studies have shown that the main peptide component of BV, melittin, has an anti-cancer effect (12,13). Melitin is a non-specific cytolytic peptide that can break down lipid bilayers and is toxic when injected (14). However, via an optimized nanoparticle-based approach, it exhibits anti-cancer effects on several cancer cells, including leukemia, liver cancer, lung cancer, and prostate cancer cells (15).…”
Section: Discussionmentioning
confidence: 99%
“…Many plant toxins, including saporin and ricin, are ribosome-inactivating proteins [4]. Animal toxins display an array of cytotoxic activity, ranging from membranolysis (melittin from Apis mellifera) [5] to chloride channels blocking (chlorotoxin from Leiurus quinquestriatus) [6]. Antimicrobial peptides, some of them known as anticancer peptides, promote cell lysis through pore formations [7].…”
Section: Introductionmentioning
confidence: 99%